London's waterfront and its world, 1666-1800 - Schofield, John; Freeth, Stephen; Betts, Ian M.; Blackmore, Lyn; Bowsher, Julian; Pearce, Jacqueline; Pipe, Alan (2023)
This volume, covering the period 1666-1800, considers the archaeology of the port of London on a wide scale, from the City down the Thames to Deptford. During this period, with the waterfront at its centre, London became the hub of the new British empire, contributing to the exploitation of people from other lands known as slavery.